2021
DOI: 10.4149/gpb_2020038
|View full text |Cite
|
Sign up to set email alerts
|

miR-133a-3p inhibits the osteogenic differentiation of bone marrow mesenchymal stem cells by regulating ankyrin repeat domain 44

Abstract: In this study, we aimed to identify the specific microRNAs (miRNAs) that are involved in the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) from ovariectomized (OVX) mice, and to further explore the mechanism by which these miRNAs regulate osteogenic differentiation. Based on the existing studies, the expression of seven miRNAs in BMSCs from OVX mice was evaluated using quantitative reverse transcription polymerase chain reaction (qRT-PCR). The expression of miR-133a-3p and osteogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In callus tissue, miR-133a-3p levels correlated negatively with Met expression ( Bourgery et al, 2021 ). Recent data indicates that overexpression of miR-133a-3p inhibits osteogenesis of bone marrow mesenchymal stem cells by regulating ankyrin repeat domain 44 ( Ankrd44 ) ( Li et al, 2021 ). Based on these previous studies, we propose that miR-133a-3p functions as a regulator of bone remodelling via targeting P13K/AKT to regulate osteogenic differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…In callus tissue, miR-133a-3p levels correlated negatively with Met expression ( Bourgery et al, 2021 ). Recent data indicates that overexpression of miR-133a-3p inhibits osteogenesis of bone marrow mesenchymal stem cells by regulating ankyrin repeat domain 44 ( Ankrd44 ) ( Li et al, 2021 ). Based on these previous studies, we propose that miR-133a-3p functions as a regulator of bone remodelling via targeting P13K/AKT to regulate osteogenic differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that both upregulation as well as downregulation of several miRNAs and differential patterns of osteogenesis have been reported in different Jagged1-exposed cell types by a number of researchers [ 35 37 ]. Thus, Li et al [ 35 ] found overexpression of mhesiR-133a-3p markedly inhibited the expression of osteogenesis-associated genes such as RUNX2 and OSX , reduced ALP activity and mineralization by targeting ankyrin repeat domain 44 (ANKRD44) in BMMSCs. Similarly, Deng et al [ 36 ] observed significant inhibition of osteogenic differentiation, cell migration, and cell proliferation in MC3T3-E1 cells due to miR-210-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miRNAs can modulate the progression of various diseases, including OP [ 39 ]. Mao et al found that miR-133a-3p regulates osteogenic differentiation by regulating the repeat domain of ankyrin [ 40 ]. MiR-133a-3p is also targeted by the lncRNA MEG3 to inhibit osteogenic differentiation during the progression of postmenopausal OP [ 29 ].…”
Section: Discussionmentioning
confidence: 99%